2017
DOI: 10.1038/s41598-017-00162-3
|View full text |Cite
|
Sign up to set email alerts
|

Region specific Raman spectroscopy analysis of the femoral head reveals that trabecular bone is unlikely to contribute to non-traumatic osteonecrosis

Abstract: Non-traumatic osteonecrosis (ON) of the femoral head is a common disease affecting a young population as the peak age of diagnosis is in the 40 s. The natural history of non-traumatic ON leads to a collapse of the femoral head requiring prosthetic replacement in a 60% of cases. Although trabecular bone involvement in the collapse is suspected, the underlying modifications induced at a molecular level have not been explored in humans. Here, we examine changes in the molecular composition and structure of bone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
3
26
1
1
Order By: Relevance
“…Pascart T et al . 22 detected a decrease in proteoglycan content in the sclerotic region, which was linked to an increase in bone remodelling. In addition, their histological examination showed the presence of woven bone corresponding to rapid disorganised new bone apposition.…”
Section: Discussionmentioning
confidence: 90%
“…Pascart T et al . 22 detected a decrease in proteoglycan content in the sclerotic region, which was linked to an increase in bone remodelling. In addition, their histological examination showed the presence of woven bone corresponding to rapid disorganised new bone apposition.…”
Section: Discussionmentioning
confidence: 90%
“…Several authors have conducted experiments using resected femoral heads with end‐stage ONFH to explore the mechanism of femoral head collapse. Wang et al showed that the micromechanical properties of bone trabeculae in collapsed femoral heads with ONFH did not differ significantly between the necrotic zone and the healthy zone.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that the micromechanical properties of bone trabeculae in collapsed femoral heads with ONFH did not differ significantly between the necrotic zone and the healthy zone. Using Raman spectroscopy analyses, Pascart et al also demonstrated that the molecular composition and structure of the trabecular bone were not modified in end‐stage ONFH. Although clarifying the mechanism of collapse would ideally involve a variety of experiments, it is impossible to obtain a whole femoral head before collapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations